Anatomical factors associated with the lingual fracture pattern in sagittal split ramus osteotomy: A case-control study - Thalles Moreira Suassuna; Elenisa Glaucia Ferreira dos Santos; Sérgio Murilo Cordeiro de Melo Filho; Carla Cecília Lira Pereira de Castro; Tatiane Fonseca Faro; Fernanda Souto Maior dos Santos Araújo; Allan Vinícius Martins-de-Barros; Fábio Andrey da Costa Araújo (PLoS ONE, 2025)
Unfavorable fractures are among the most challenging complications in sagittal split ramus osteotomy (SSRO), potentially increasing surgical morbidity and compromising postoperative outcomes. The preoperative identification of anatomical risk factors through imaging can enhance surgical planning and prevent such events. This study aims to investigate the anatomical factors associated with lingual fracture patterns in SSRO using multislice computed tomography. This retrospective case-control study included 180 mandibular rami from patients who underwent SSRO at a Clinical Research Center for Oral and Maxillofacial Surgery. Fractures were classified according to Plooij (2009), with Types 3 and 4 grouped as cases and Types 1 and 2 as controls. Linear measurements of mandibular ramus thickness, the distance between the mandibular canal and the buccal cortical bone, as well as parameters related to the mandibular lingula were analyzed. The case group showed significantly thinner mandibular bone (p < 0.001) and a shorter canal-cortical distance (p = 0.013), suggesting a direct association between these anatomical variables and unfavorable fracture patterns. Bonferroni post hoc analysis revealed no significant difference between fracture patterns Type 3 and Type 4 (p = 1.000), supporting their grouping in a single analytical category. The presence of third molars was not significantly associated with fracture patterns (p > 0.05). These results underscore the importance of anatomical parameters in predicting the risk of unfavorable fractures. Specifically, reduced bone thickness and proximity of the mandibular canal play a crucial role in the occurrence of unfavorable SSRO fractures. Preoperative evaluation using computed tomography is essential to optimize surgical planning and minimize complications. However, given the limitations of retrospective designs potential biases are acknowledged, and further prospective studies are needed to confirm these findings and improve risk assessment in SSRO.